Food for Thought incorporating food security dimensions in ZFarm designs for Philippine urban spaces - Katague, Kamille Noriel A.
The global trends point to a continuing rapid population growth and increase in urban population which makes it imperative to find more sustainable ways to provide space, food, and other resources for the future. In light of these events and predictions, Zero-Acreage Farming or ZFarming is gaining traction as it offers untouched rooftops and other idle spaces in and around buildings as produce-generating structures, effectively utilizing the space and providing other benefits to its users and surroundings. However, support on the ordinary people's ZFarm practices does not stop in the mere provision of space and produce seeds because to improve food security, the people need to have physical, social, and economic access to sufficient, safe, and nutritious food at all times. This research aims to provide a design guide for small, medium and large scale housing for the ZFarming for urban living quality type in the context of Philippine urban spaces. Barangay Commonwealth, Quezon City is chosen as the location of the study where most of the city population resides and still exhibits characteristics of a highly urbanized area. Here, we designate areas according to the scales and create a design template according to the beneficiaries' needs. By producing a comprehensive guide for ZFarming for urban living quality type, the research gives light on the requirements of a proper ZFarm to address all dimensions of food security and encourage support from the government and interest from the public.